PENGENALAN INOVASI LEKSIKAL BAHASA MELAYU RIAU PADA MASYARAKAT LIMBUNGAN KECAMATAN RUMBAI PESISIR - Yani, Juli (EDUTECH CONSULTANT, 2017)
Community service is titled Introduction to Programming Lexical Malay Riau on Urban Village Community Limbungan Rumbai Coastal District of the city of Pekanbaru. The main problems faced by the partners are many variations of innovation lexical Malay Riau in Sub Limbungan District of Rumbai Coastal caused many Village community Limbungan District of Rumbai coastal city of Pekanbaru who married someone outside the village Limbungan District of Rumbai Coastal and go out or leave. The purpose of this devotion is through training on the introduction of lexical innovation, are expected to provide knowledge and understanding of innovation lexical variation in the Riau Malay Village community Limbungan Rumbai Coastal District of the city of Pekanbaru. Ibm Community activities carried out to villages in District Rumbai Limbungan and Coastal. The number of people who will participate in this training 20 people.